Clinical and radiological characteristics of mediastinal melioidosis: A four-year retrospective cohort from Sabah, Malaysia - Larry Ellee Nyanti; Muhammad Zahid Abdul Muien; Amalina Abu Othman; Chia, Yen Lik; Mahabalraj Singh Peshi; Valerie Toh; Nur Siti Fatimah Mohamad Jamil; Meryl Grace Lansing; Huan, Nai Chien; Hema Yamini Ramarmuty; Kunji Kannan Sivaraman Kannan (Elsevier, 2024)
Background Melioidosis is a potentially fatal tropical infection. Little is known about mediastinal involvement in melioidosis. This study aimed to (a) describe the prevalence and demographics of various morphologies of mediastinal melioidosis, (b) propose a classification for radiological morphologies of mediastinal melioidosis. Methods A retrospective cohort study was performed. Case records of consecutive patients with culture-positive melioidosis who underwent computed tomography (CT) thorax from January 1, 2018–February 28, 2022, were reviewed. Results 486 culture-positive melioidosis patients were identified, of which 70 underwent CT thorax. 41 patients demonstrating mediastinal involvement were included in the final analysis, of which four were mediastinal collections, while the rest were classified into those with necrotic or matted appearances, and subcentimeter and larger than 1 cm. Culture-positivity was proven from blood in 83 % of patients (n = 34), with the remaining from chest wall pus, neck abscess pus, sputum, liver abscess, seminal vesicle, pleural, pericardial and peritoneal fluid. The most commonly associated pulmonary manifestations were consolidation and pleural effusion. Half had diabetes; a quarter had chronic kidney disease, while one had syphilis. Exposure to soil was present in six patients: quarry (n = 1), construction (n = 2), farmer (n = 1), living environment (n = 2). Seven patients succumbed before the end of 6-week intensive phase antibiotic treatment. Conclusion Mediastinal melioidosis is a spectrum with multiple overlapping features consisting of necrosis, matted lymph nodes, multiseptated and non-septated collections. Further studies will elucidate the prognostic implications of mediastinal melioidosis.